Impact of Diabetes Mellitus on Peripheral Vascular Disease Concomitant with Coronary - Mehrab Marzban; Mohammadreza Zafarghandi; Mohsen Fadaei Araghi; Abbasali Karimi; Seyed Hossein Ahmadi; Namvar Movahedi; Kyomars Abbasi; Naghmeh Moshtaghi (Journal of Tehran University Heart Center, 2009)
Background: The aim of this study was to evaluate the impact of diabetes mellitus (DM) on peripheral vascular disease (PVD) in patients with coronary artery disease (CAD).